Enhancing Patient Outcomes in Intensive Care Units: The Impact of Multidisciplinary Team Collaboration on Care Quality (The Review of Diabetic Studies, 2025)
Background: Intensive care units (ICUs) manage critically ill patients who require complex, high-risk, and time-sensitive interventions. The growing complexity of care delivery has highlighted the need for collaborative, team-based approaches to ensure safe, efficient, and high-quality care. Multidisciplinary team collaboration has emerged as a core strategy for addressing clinical complexity, reducing variability in care, and improving patient-centered outcomes within ICU settings.Objective: This review aims to synthesize current evidence on the impact of multidisciplinary team collaboration on care quality and patient outcomes in intensive care units, focusing on clinical, organizational, and safety-related dimensions of care.Methods: A narrative integrative review of peer-reviewed literature published between 2016 and 2025 was conducted using major medical and health science databases. Studies examining collaborative care models, interprofessional communication, shared decision-making, and coordinated clinical workflows in ICUs were included.Results: The evidence consistently demonstrates that effective multidisciplinary collaboration in ICUs is associated with improved patient outcomes, including reduced mortality, shorter length of stay, enhanced patient safety, and better adherence to evidence-based practices. Additionally, collaborative models contribute to improved workflow efficiency, reduced medical errors, and higher staff satisfaction.Conclusion: Multidisciplinary team collaboration plays a critical role in enhancing the quality of care in intensive care units. Strengthening interprofessional communication, shared accountability, and coordinated clinical decision-making is essential for optimizing patient outcomes and sustaining high-performance ICU environments.